Role of Helicobacter Pylori in Chronic Urticaria among Egyptian Patients with Dyspepsia: A case-control study - Al-Sadat Mosbeh (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2017)
Background/Objective: Chronic urticaria is one of the most frequent skin diseases and still its etiology is recognized only in a minority of cases. Some recent studies point out to infections due to Helicobacter Pylori as being of major importance in the pathogenesis of chronic urticaria. This study aimed to fi nd out the association of chronic urticaria with H. pylori. Patients and methods: A case-control study was conducted in cairo within the period of Jan 1st, 2016 to January 1st, 2017. The study included 100 cases with chronic urticaria and 100 controls that were free from features of chronic urticaria. Data was collected through direct interview and the results of laboratory investigations were recorded in a specially designed questionnaire. Enzyme-linked immunosorbent assay test was used for detection of Helicobacter pylori antigen in the stool sample. Also gastric endoscope and gastric biopsys were done in addition to histopathological assessment by H&E and Geimsa stain for detection of Helicobacter Pylori. Endoscope was done for patient who was positive stool antigen test. Triple therapy were given for patients in addition to antihistamine to evaluated effect of eradication for helicobacter pylori on chronic urticaria Results: The age of the 100 cases and 100 controls enrolled ranged from 18 to 67 years.Stool for Helicobacter pylori antigen test was positive in 65% of cases and 29% of controls (P <0.05). The mean age ± SD of positive Helicobacter pylori patients were 33.2 ± 10.4 years, with male to female ratio 1:1.69.  Conclusion: There was a strong association of chronic urticaria with Helicobacter pylori infection. Investigating for Helicobacter pylori in all cases of chronic urticaria and conducting further trials on Helicobacter pylori eradication is recommended.